Dysplasia and PNH‐type cells in bone marrow aspirates of myelodysplastic syndromes. Issue 2 (22nd November 2021) - Westers, Theresia M.; Alhan, Canan; Visser‐Wisselaar, Heleen A.; Chitu, Dana A.; van de Loosdrecht, Arjan A.
Abstract: Background: Flow cytometry is increasingly applied in cytopenic patients suspected for myelodysplastic syndromes (MDS). Analysis includes evaluation of antigen expression patterns in granulocytes of which, for example, partial lack of CD16 may indicate dysplasia, but presence of paroxysmal nocturnal hemoglobinuria (PNH)‐type cells should be considered. However, diagnostic bone marrow (BM) samples hamper PNH analysis because immature stages in the granulo‐/monocytic compartment lack expression of certain glycophosphatidyl‐inositol‐anchored proteins. In this prospective study, we evaluated the presence of PNH‐type cells in BM next to aberrancies from routine MDS immunophenotyping. Methods: We combined antibodies defining maturation trajectories with FLAER. Validation of the designed method against routine PNH analysis and parallel analysis of BM and blood samples revealed similar results (granulocytes: Wilcoxon p  = 0.25 and p  = 0.82, respectively). We analyzed BM samples from 134 MDS, 17 chronic myelomonocytic leukemia, 15 aplastic anemia (AA), 1 PNH, 51 non‐clonal cytopenic controls, and 12 normal controls. Results: Most AA/PNH‐BM samples showed clear PNH clones: median 1.1% (0%–35%); CD16 loss on mature neutrophils paralleled PNH‐clone sizes. In MDS‐BM, only 3.7% of cases showed ≥0.1% PNH‐type cells, whereas partial CD16 loss was more frequent and abundant. Conclusions: Our findings confirm that dysplastic features in MDS‐BM may point to presence of PNH‐type cells, though only few cases displayed FLAER‐negative cells. We showed that identification of these cells in the granulocyte compartment of BM specimen is feasible, but—according to international guidelines—results need to be confirmed in peripheral blood.